Concepts in Federal Taxation 2020, 27th Edition - Kevin E. Murphy; Mark Higgins (Cengage Learning, 2019)
Master the concepts behind today's federal taxation using the balanced, conceptual approach found only in Murphy/Higgins' CONCEPTS IN FEDERAL TAXATION 2020. You examine the latest tax codes and most recent changes for the current tax year using the book's clear, straightforward approach that's specifically crafted to help you prepare for success on the CPA Exam. You learn the unifying concepts behind the Internal Revenue Code rather than memorizing details of the Code. Concepts and applications throughout this edition appear in brief, comprehensible segments that are ideal for your CPA Exam review. In addition, meaningful examples relate concepts to familiar business scenarios with more opportunities for practice than any other book of this kind to further strengthen your understanding of federal taxation. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.